Farmer-Herder Conflict and National Security in Nigeria: The Benue State in Perspective - Ioryue, Dominic Aondowase (Kashere Journal of Politics and International Relations, 2024)
The Farmer-Herder conflict in Nigeria has emerged as a critical challenge to national security, with its epicentre in Benue State. This study investigates the multifaceted dimensions of the conflict, its historical roots, and its implications for the broader security architecture of the country. Employing a comprehensive approach, the paper delves into the socio-economic, political, and environmental factors that contribute to the escalation of tensions between farmers and herders, unravelling a complex web of issues that threaten the stability of the State. The agrarian nature of Benue State, characterised by fertile land and a predominantly farming population, exacerbates competition for resources with nomadic herders seeking pasture for their livestock. This struggle over limited resources has intensified due to climate change impacts, population growth, and weak governance structures. The conflict not only results in loss of lives and property but also undermines social cohesion, exacerbates ethnic and religious fault lines, and poses a tremendous threat to food security. This study adopts an Environmental Security and Resource Scarcity approach as its framework. The study generated data using both primary method through interviews and secondary method through existing literature such as books, journals, internet sources, etc. The findings of the study revealed that there is a competition for scarce resources, particularly land and water, as burgeoning populations and climate change intensify the struggle between farmers and herders in Benue State. The study, therefore, recommends the development and implementation of sustainable land use policies that take into account the needs of both farmers and herders.